Claims, changes and challenges in translation studies : selected contributions from the EST Congress, Copenhagen 2001 - Hansen, Gyde; Malmkjær, Kirsten; Gile, Daniel (Benjamins translation library ;, 2004)
The volume contains a selection of papers, both theoretical and empirical, from the European Society for Translation Studies (EST) Congress held in Copenhagen in September 2001. The EST Congresses, held every three years in a different country, reflect current ideas, theories and studies covering the whole range of ""Translation"", both oral and written, and the papers collected here, authored by both experienced and young translation scholars, provide an up-to-date picture of some concerns in the field. Topics covered include translation universals, linguistic approaches to translation.